2021
DOI: 10.1002/cb.1945
|View full text |Cite
|
Sign up to set email alerts
|

Influencer marketing in China: The roles of parasocial identification, consumer engagement, and inferences of manipulative intent

Abstract: Considering trends in influencer marketing, this research explores the mechanism by which Chinese consumers develop responses to branded content on social media, especially the key psychological factors that may positively or negatively affect that process. To substantiate the proposed conceptual frameworks, we used data from a nationwide online survey (N = 511) conducted in China. The results revealed that consumers' parasocial identification with social media influencers contributed to their engagement with,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 62 publications
1
16
0
1
Order By: Relevance
“…This is due to the YouTuber's concern for the audience's welfare when providing the reviews. This result was consistent with previous studies, which found that parasocial interaction significantly impacts trust [110]. Furthermore, we looked at the relationship between parasocial interaction and information usefulness, and the findings showed that parasocial interaction has no significant effect on information usefulness (H9).…”
Section: Discussionsupporting
confidence: 91%
“…This is due to the YouTuber's concern for the audience's welfare when providing the reviews. This result was consistent with previous studies, which found that parasocial interaction significantly impacts trust [110]. Furthermore, we looked at the relationship between parasocial interaction and information usefulness, and the findings showed that parasocial interaction has no significant effect on information usefulness (H9).…”
Section: Discussionsupporting
confidence: 91%
“…Thomala's study (2021) found that most Chinese people, around 80%, follow at least one online influencer. In China, some scholars perceive online influencers as a new type of celebrity (Chen et al, 2021a(Chen et al, , 2021bFan, 2021;Hung, 2020). They develop their online personal images and charisma by updating social media feeds about their daily life, expertise and individual thoughts (Hung, 2020).…”
Section: Online Influencers and Their Prevalence In Chinamentioning
confidence: 99%
“…Online influencers are mostly self-made opinion leaders with strong popularity among social media users (Gra ¨ve, 2017;Schouten et al, 2020). In the literature of influencer studies, scholars currently use the following terms to name online influencers: social media influencers (Coates et al, 2019;Shan et al, 2020;Sundermann and Raabe, 2019), key opinion leaders (Zhu and Wang, 2020), bloggers (Balabanis and Chatzopoulou, 2019;Gannon and Prothero, 2018), vloggers (Ladhari et al, 2020;Lee and Watkins, 2016), internet celebrities (Chen et al, 2021a(Chen et al, , 2021bRoberts, 2010) micro-celebrities (Khamis et al, 2016;Martı ´nez and Olsson, 2019) and wang hong, which means popular internet figure in the Chinese context (Cheng, 2018;Xu and Zhao, 2019).…”
Section: Online Influencers and Their Prevalence In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Estos factores afectan a la confianza de sus adeptos en las publicaciones de la marca, algo que posteriormente influye en el conocimiento de la misma y en las intenciones de compra (Lou y Yuan, 2019). La identificación de los consumidores con los influenciadores, contribuye también al compromiso y a la actitud de los primeros hacia los contenidos que difunden los segundos (Chen et al, 2021). Esto puede acercar a una marca a su público objetivo rápidamente, si elige bien a los influenciadores que difundan su contenido.…”
Section: úTil Para La Nueva Empresa O Para Cualquier Empresa Que Quie...unclassified